Hemophilia: Molecular diagnosis and alternatives of treatment (2007)
The haemophilia is a recessive disease tied to the X chromosome that generally men suffer. The genetic preimplantation diagnosis (GPD), the prenatal diagnosis and the molecular diagnosis of the mutations that cause haemophilia, are realized in isolated investigations (researches) in order to do primary prevention, provide advise to the carriers of the disease and their families, which has allowed to bring to the world children free of this disease and also to improve the quality of life of the affected ones. The hopeful procedures in gene therapy (GT) have shown great effectiveness. The intention is to achieve the normal production of the protein which is absent or it is altered in the affected ones, but at the moment the tests carried out in human beings are stopped. Here are other alternate therapies that although are in phase of investigation, would allow to obtain a production of protein to long term and which have been developed thanks to the understanding of the molecular nature of the coagulation factors. © 2007 Corporación Editora Médica del Valle.